PRODUCTION OF HYBRID AND MADURA LOCAL CORN AS BABY CORN IN PAMEKASAN REGENCY - Kelik Perdana Windra Sukma; Iswahyudi Iswahyudi; Moh. Taufikurrahman (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2021)
Baby corn is corn cobs that are picked when they are very young and before the seeds are formed. Until now, there has been no research on the potential of local Madurese maize as baby corn. The use of local Madurese maize varieties as babycorn is an effort to increase the potential value of the commodity in order to increase farmers' income sources. Plants were planted in paddy fields using a randomized block design plot. Maintenance of corn plants using corn planting standards. Parameters observed included: plant height, stem diameter, number of leaves, age of flowering, harvest age, harvest period, ear wet weight, ear length, ear diameter, and ear sugar content. Data analysis used SPSS 16. The results of the analysis showed that there were differences in height and stem diameter of hybrid maize plants with local Madurese varieties but between local Madurese varieties showed no significant differences except for the growth in the number of leaves. Flowering age, early harvest age, and harvest period produced very significant differences.